The Role of Innovation Hubs in Accelerating Circular Economies: Business Model Innovation and Cross-Sector Collaboration (A Systematic Review) - Aderinsola E. Kayode and Abraham O Adeniran (Researchers World - International Refereed Social Sciences Journal, 2025)
Purpose: The study aims to explore the systematic review the critical role of innovation hubs in accelerating the transition to circular economies (CE) by fostering innovation, collaboration, and the development of sustainable business models in which to understand the mechanisms through the innovation hubs fostere circular thinking and to identify the conditions under which they most effectively drive systemic change toward a more regenerative economic framework. Methodology: By analysing 11 peer-reviewed studies, this review identifies several key themes, including business model innovation for the circular economy (BMI4CE), the adoption of Industry 4.0 technologies, and the importance of cross-sector collaboration. Innovation hubs facilitate the integration of circular principles by supporting startups and established businesses in experimenting with circular models, implementing advanced technologies such as blockchain and IoT, and encouraging collaboration across industries. However, significant challenges remain, including regulatory and financial barriers, constraints in technological adoption, and the need for greater consumer engagement. Findings: The review highlights that while innovation hubs provide essential platforms for knowledge sharing and partnership, addressing these barriers is crucial for scaling circular economy practices. Policy implications are discussed, emphasizing the need for cohesive regulatory frameworks, financial support mechanisms for circular startups, and initiatives to increase consumer awareness and participation. Originality: The current research makes a significant contribution to current literature and also contributes to a deeper understanding of how innovation hubs can accelerate circular economy initiatives, offering insights for policymakers, businesses, and academics.